2021
DOI: 10.3390/cells10112880
|View full text |Cite
|
Sign up to set email alerts
|

Instructions for Flow Cytometric Detection of ASC Specks as a Readout of Inflammasome Activation in Human Blood

Abstract: Inflammasome activation is linked to the aggregation of the adaptor protein ASC into a multiprotein complex, known as the ASC speck. Redistribution of cytosolic ASC to this complex has been widely used as a readout for inflammasome activation and precedes the downstream proteolytic release of the proinflammatory cytokines, IL-1β and IL-18. Although inflammasomes are important for many diseases such as periodic fever syndromes, COVID-19, gout, sepsis, atherosclerosis and Alzheimer’s disease, only a little knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The inflammasome activation involves cleavage of caspase-1 through the use of a scaffolding adaptor protein known as the apoptosis-associated speck-like protein containing a caspase recruiting domain (ASC), which oligomerizes to form an ASC speck. ASC specks bind to caspase-1, resulting in the formation of the inflammasome complex [28][29][30][31] and downstream activation of the pro-inflammatory cytokines interleukin (IL)-18 and IL-1β [32].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammasome activation involves cleavage of caspase-1 through the use of a scaffolding adaptor protein known as the apoptosis-associated speck-like protein containing a caspase recruiting domain (ASC), which oligomerizes to form an ASC speck. ASC specks bind to caspase-1, resulting in the formation of the inflammasome complex [28][29][30][31] and downstream activation of the pro-inflammatory cytokines interleukin (IL)-18 and IL-1β [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, after evaluation of various pre-analytical conditions (type of anticoagulant, temperature and sample storage time, etc. ), Wittman and his team provided technical recommendations regarding ASC specks detection in human PBMCs [ 16 ]. In order to facilitate clinical explorations, Cui et al reported a whole blood protocol without any subsequent ex vivo stimulation to study in vivo NLRP3 inflammasome activation level [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the local ethics committee (BB 014/18; BB 158/19; BB 188/20; BB032/21). After coagulation was complete, the serum was centrifuged for 10 min at 1,000 g. Peripheral blood mononuclear cells (PBMCs) were isolated from blood using density gradient centrifugation as previously described (12).…”
Section: Patient Acquisition and Blood Sample Processingmentioning
confidence: 99%
“…For longer storage of fixed cells, we recommend a washing step and storage of samples in PBS. Cells were stained and measured on the next day as previously described (12).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation